AN INTERESTING CASE OF FISH ENVENOMATION - DR.SENTHIL RAJ THANGASAMI, MD (GEN),; DR.THANGASAMI, MD (GEN), (International Journal of Pharma and Bio Sciences, 2016)
Aquariums are very popular and keeping fish tanks in homes and business places is a very common practice. Spotted scat is a popular aquarium fish and it is also used commonly as an edible fish in Indo-pacific region. Its envenomation can occur accidentally and most cases go unreported. Scat fish sting can produce severe pain, swelling, redness, fever, partial paralysis and throbbing sensation in the inflicted site. There is no much information about the venom constituents, pharmacology and venom antagonist. Except for a few symptomatic treatments, no specific treatment is available to treat the patient